Stimulated emission at 257 nm from optically‐pumped AlGaN/AlN heterostructure on AlN substrate. Issue 9 (21st May 2013) - Lochner, Zachary; Li, Xiao‐Hang; Kao, Tsung‐Ting; Satter, Md. Mahbub; Kim, Hee Jin; Shen, Shyh‐Chiang; Yoder, P. Douglas; Ryou, Jae‐Hyun; Dupuis, Russell D.; Sun, Kewei; Wei, Yong; Li, Ti; et al.
<x xml:space="preserve">Abstract</x> Optically pumped deep‐ultraviolet lasers operating at room temperature are demonstrated from heterostructures consisting of AlxGa1−xN/AlN grown on (0001) AlN substrate. The substantial reduction of the threading dislocation density by using a native AlN substrate over sapphire substrates is critical to the realization of the photo‐pumped lasers. The threshold power density was 1.88 MW cm−2. The layers below the active region were Si‐doped and had bottom waveguide and cladding layer n‐type structures required for diode lasers, thus demonstrating the feasibility of deep UV lasing for the proposed structures on AlN substrates by current injection, provided that effective hole injection layers are included.